The effects of problem-based learning during medical school on physician competency: a systematic review - Koh, G. C.-H.; Khoo, H. E.; Wong, M. L.; Koh, D. (Canadian Medical Association journal (CMAJ), 2008)
Systematic reviews on the effects of problem-based learning have been limited to knowledge competency either during medical school or postgraduate training. We conducted a systematic review of evidence of the effects that problem-based learning during medical school had on physician competencies after graduation. We searched MEDLINE, EMBASE, CINAHL, PsycINFO, Cochrane Databases, and the tables of contents of 5 major medical education journals from earliest available date through Oct. 31, 2006. We included studies in our review if they met the following criteria: problem-based learning was a teaching method in medical school, physician competencies were assessed after graduation and a control group of graduates of traditional curricula was used. We developed a scoring system to assess the quality of the studies, categorized competencies into 8 thematic dimensions and used a second system to determine the level of evidence for each competency assessed. Our search yielded 102 articles, of which 15 met inclusion criteria after full text review. Only 13 studies entered final systematic analysis because 2 studies reported their findings in 2 articles. According to self-assessments, 8 of 37 competencies had strong evidence in support of problem-based learning. Observed assessments had 7 competencies with strong evidence. In both groups, most of these competencies were in the social and cognitive dimensions. Only 4 competencies had moderate to strong levels of evidence in support of problem-based learning for both self-and observed assessments: coping with uncertainty (strong), appreciation of legal and ethical aspects of health care (strong), communication skills (moderate and strong respectively) and self-directed continuing learning (moderate). Problem-based learning during medical school has positive effects on physician competency after graduation, mainly in social and cognitive dimensions.